Ensino Religioso e BNCC - GLÓRIA, Rosileide Batista (Universidade Federal do Tocantins, 2023)
The proposal of Religious Education (RE) in the National Common Curricular Base (BNCC) has a non-denominational character, a reason that highlights even more the problem around the interests that historically circumvented and circumvents Brazilian education. This article aims to discuss the first curriculum document proposed by the Ministry of Education, at the national level, which guides the provision of Religious Education: the National Curricular Common Base (BNCC). This research is justified by bringing to light the process of discussion of Religious Education in Brazilian legislation, considering the different discussions until its implementation in schools after the approval of the BNCC. It is interesting to note that, throughout the history of Brazilian education, the BNCC was the first curriculum document whose writing was considered a popular consultation. The permanence of Religious Education can be the first step to resolve doubts that arose during the process of organizing its controversial content, leading the Ministry of Education to consider that it, under some model, can contribute to the formation and exercise of religious education. citizenship.